The hidden potential of the bambara groundnut - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The bambara groundnut (Vigna subterranea (L.) Verdc.) is grossly undervalued in Africa, according to Gaebewe Ramolemana, lecturer in soil fertility at the University of Botswana. The bambara groundnut, a relative of the cowpea, is a protein-rich...